Thrombospondin 1 Is Increased in the Aorta and Plasma of Patients With Acute Aortic Dissection - Zeng, Tao; Yuan, Jun; Gan, Jianting; Liu, Yu; Shi, Lei; Lu, Zhengde; Xue, Yan; Xiong, Rixin; Huang, Min; Yang, Zicong; Lin, Yingzhong; Liu, Ling (Canadian journal of cardiology, 2019)
Previous studies have shown that thrombospondin 1 (TSP-1) is involved in cardiovascular diseases, such as atherosclerosis and abdominal aortic aneurysm. However, TSP-1 expression levels in human aortic dissection (AD) remain unknown. TSP-1 levels were detected in aortas collected from control subjects and AD patients. The TSP-1, interleukin (IL) 6, matrix metalloproteinase (MMP) 2, and MMP9 levels in plasma from non-AD patients and AD patients were measured. In addition, the effects of recombinant mouse TSP-1 protein on macrophage differentiation and smooth muscle cell (SMC) apoptosis were investigated. Compared with the aortas from control subjects, aortas from AD patients showed a significant increase in TSP-1 expression, especially in the torn sections. SMCs and endothelial cells produced TSP-1, but SMCs were the main source. TSP-1, IL-6, MMP2, and MMP9 levels were higher in AD patients than in non-AD patients, and plasma IL-6, MMP2, and MMP9 levels were positively correlated with TSP-1 levels in AD patients. Simple linear regression analysis and multivariate linear regression analysis showed that TSP-1 levels were independently correlated with the onset of AD. In cultured cells, recombinant mouse TSP-1 further increased inducible nitric oxide synthase (iNOS) mRNA expression in angiotensin (Ang) II-treated macrophages, whereas it reduced B-cell lymphoma-2 (Bcl2) mRNA levels and increased Bcl2-associated X protein (Bax) mRNA levels in Ang II-treated SMCs. TSP-1 level is significantly increased in AD patients and might participate in AD via promoting classically activated macrophage (M1) macrophage differentiation and SMC apoptosis. Des études antérieures ont montré que la thrombospondine-1 (TSP-1) joue un rôle dans les maladies cardiovasculaires comme l’athérosclérose et l’anévrisme de l’aorte abdominale. Toutefois, les taux d’expression de la TSP-1 chez les patients présentant une dissection aortique (DA) demeurent inconnus. Les concentrations de TSP-1 ont été mesurées dans des aortes prélevées chez des sujets témoins et des patients présentant une DA. Les concentrations plasmatiques de TSP-1, d’interleukine-6 (IL-6) et de métalloprotéase matricielle-2 et -9 (MMP-2 et MMP-9) ont été mesurées chez des patients atteints de DA et chez des patients non atteints. De plus, nous avons étudié les effets de la protéine TSP-1 murine recombinante (rmTSP-1) sur la différenciation des macrophages et sur l’apoptose des cellules des muscles lisses (CML). Comparativement à celles des sujets témoins, les aortes des patients ayant une DA présentaient une augmentation marquée de l’expression de la TSP-1, en particulier dans les sections déchirées. Les CML et les cellules endothéliales produisaient de la TSP-1, mais les CML en constituaient la source principale. Les concentrations de TSP-1, d’IL-6, de MMP-2 et de MMP-9 étaient plus élevées chez les patients atteints de DA que chez les patients non atteints, et une corrélation positive entre les taux plasmatiques d’IL-6, de MMP-2 et de MMP-9 et ceux de TSP-1 a été observée chez les patients atteints de DA. Les analyses de régression linéaire simple et multivariée ont montré que les concentrations de TSP-1 étaient indépendamment corrélées à la survenue d’une DA. Dans des cellules en culture, la TSP-1 de souris recombinante a de plus provoqué une augmentation de l’expression de l’ARNm de l’oxyde nitrique synthase inductible (iNOS) dans les macrophages traités par l’angiotensine II, alors qu’elle réduisait les concentrations d’ARNm de la protéine Bcl-2 et augmentait les concentrations d’ARNm de la protéine Bax dans les CML traitées par l’angiotensine II. La TSP-1 est présente à des concentrations significativement plus élevées chez les patients atteints de DA et pourrait participer à la DA en stimulant la différenciation des macrophages M1 et l’apoptose des CML.